The predictors of mortality in IPF - Does emphysema change the prognosis? - Tokgoz Akyıl, Fatma; Sevim, Tülin; Akman, Canan; Aksoy, Emine; Ağca, Meltem; Aktas, Oguz; Akyıl, Mustafa (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Combined idiopathic pulmonary fibrosis (IPF) and emphysema (CPFE) has been reported to be more common in male smokers. A number of studies comparing CPFE patients with fibrosis-only patients have reported a similar prognosis while others have reported a significantly shorter survival. Objectives: In present study, we aimed to compare baseline characteristics of patients with IPF according to emphysema presence. We asssessed the prognostic value of emphysema along with each other parameter. Methods: We retrospectively reviewed the clinical, baseline radiological, laboratory and physiological parameters of 92 patients who were diagnosed with IPF. The patients were divided into two groups: those without emphysema (Group 1) and with emphysema (Group 2). All-cause mortality was recorded, and the impact of the variables on survival was evaluated. Results: Emphysema was recorded in 23 patients, all of whom were male. While ever-smoker rate was higher in Group 2 laboratory and physiologic parameters were similar. Radiologically, the presence of honeycombing, ground glass opacity, the extension and symmetry of involvement did not differ between the Groups. The median survival time was 29±4 months. Patients in Group 1 and 2 had a median survival of 34 and 9 months, respectively. In univariate analysis; radiological presence of emphysema and honeycombing, male gender, lower baseline levels of albumin and oxygen saturation, forced vital capacity and carbon monoxide diffusing capacity were detected as predictors of mortality. Conclusion: In present study, IPF with emphysema was more common in male smokers. When emphysema accompanies IPF, life expectancy is remarkably worse, but not independently so.